IDENTIFIKASI JAMUR MAKROSKOPIS DI KAWASAN HUTAN KAMPUS UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Try Susanti; Zahra Zami Amalia P; Zalfa Fildzah Liani; Nur Hafizhoh; Salatipah Husna Sinawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Macroscopic fungi are an important component of a forest ecosystem, acting as natural decomposers and supporting nutrient cycles. The Campus Forest Area of ​​the State Islamic University of Sulthan Thaha Saifuddin Jambi has a supportive environment for the growth of various macroscopic fungal species, but information regarding the diversity of these macroscopic fungi is still very limited. This study was conducted with the aim of determining the diversity of macroscopic fungi in the campus forest area. The method used in this study was exploration with direct observation techniques and documentation of samples found at several points in the research location. Identification of macroscopic fungi was carried out by observing morphological characteristics including fruiting body shape, size, color, hymenophore type, and the substrate where they live. The data obtained were analyzed descriptively. The results of the study indicate that the campus forest area of ​​the State Islamic University of Sulthan Thaha Saifuddin Jambi is covered by various types of macroscopic fungi belonging to several diverse families and genera. Several types of fungi were found growing on decaying wood substrates, dead tree trunks, leaf litter, and moist soil. The presence of macroscopic fungi in this area is influenced by various factors, such as temperature, humidity, and the availability of organic matter. This research is expected to provide a baseline source of information on macroscopic fungal diversity and the development of biodiversity research on campus.